2022
DOI: 10.1215/00703370-10085223
|View full text |Cite
|
Sign up to set email alerts
|

Sexualities and Geographic Mobility Between Childhood and Adulthood in the United States

Abstract: Though research suggests that sexual minorities (e.g., nonheterosexual individuals) are more geographically mobile in the transition to adulthood than their heterosexual counterparts, quantitative estimates are rare and previously used data sources have significant limitations. Using data from the National Longitudinal Study of Adolescent to Adult Health (N = 11,705) that directly measure sexualities across dimensions (i.e., identity, behavior, and attraction), I examine variation in geographic mobility betwee… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 64 publications
0
2
0
Order By: Relevance
“…Along similar lines, we found that LGBT respondents also experienced greater changes to their family and social support. Such findings may reflect the greater geographic mobility of LGBT persons relative to heterosexual persons [37], further challenging their kin access during COVID-19 restrictions.…”
Section: Discussionmentioning
confidence: 99%
“…Along similar lines, we found that LGBT respondents also experienced greater changes to their family and social support. Such findings may reflect the greater geographic mobility of LGBT persons relative to heterosexual persons [37], further challenging their kin access during COVID-19 restrictions.…”
Section: Discussionmentioning
confidence: 99%
“…LGB people appear to have fewer family contacts and confidants than heterosexuals (Dewaele et al, 2011; Fischer, 2022), report significant effort needed to maintain ties with parents (Bosley‐Smith & Reczek, 2022), and tend to rank social support from friends as more consistent and more important than support from family (Graham & Barnow, 2013; Lyons et al, 2013). Further, gay and lesbian individuals have greater geographic distance from parents relative to other sexual identity groups, suggesting less secure ties (Levine, 2022). Given this large body of work, it is likely that LGB adults are more likely to experience estrangement from parents than heterosexual children, and this may be especially true for the paternal tie given research showing that fathers are more likely to have homophobic reactions to their children than mothers (Bucher, 2014; Stacey, 2021; Stacey & Padavic, 2021).…”
Section: Introductionmentioning
confidence: 99%